Role of adaptive and non-adaptive mechanisms forming complex patterns of genome size variation in six cytotypes of polyploid Allium oleraceum (Amaryllidaceae) on a continental scale - Duchoslav, Martin; Šafářová, Lenka; Jandová, Michaela (Annals of botany, 2013)
BACKGROUND AND AIMS: Although the large variation in genome size among different species is widely acknowledged, the occurrence and extent of variation below the species level are still controversial and have not yet been satisfactorily analysed. The aim of this study was to assess genome size variation in six ploidy levels (2n = 3x-8x) of the polyploid Allium oleraceum over a large geographical gradient and to search for potential interpretations of the size variation. METHODS: The genome sizes of 407 individuals of A. oleraceum collected from 114 populations across Europe were determined by flow cytometry using propidium iodide staining. The genome size variation was correlated with spatial, climatic and habitat variables. KEY RESULTS: The mean holoploid genome size (2C DNA) was 42·49, 52·14, 63·34, 71·94, 85·51 and 92·12 pg at the tri-, tetra-, penta-, hexa-, hepta- and octoploid levels, respectively. Genome size varied from a minimum of 2·3 % in the octoploids to a maximum of 18·3 % in the tetraploids. Spatial structuring of genome size was observed within the tetra- and pentaploids, where 2C DNA significantly increased with both latitude and longitude, and correlated with several climatic variables, suggesting a gradient of continentality. Genome size in hexaploids showed low variation, weak correlation with climatic variables and no spatial structuring. Downsizing in monoploid genome size was observed between all cytotypes except for heptaploids. Splitting populations into western and eastern European groups resulted in strong differences in monoploid genome size between groups in tetra- and pentaploids but not in hexaploids. The monoploid genome sizes of the cytotypes were similar in the western group but diverged in the eastern group. CONCLUSIONS: Complex patterns of holoploid and monoploid genome size variation found both within and between A. oleraceum cytotypes are most likely the result of several interacting factors, including different evolutionary origins of cytotypes via hybridization of parental combinations with different genome sizes in the south-western and south-eastern part of Europe, introgression between cytotypes, and antropic dispersal. The role of broad-scale and fine-scale environmental variables in shaping genome size is probably of minor importance in A. oleraceum.
Keywords: Europe; DNA, Plant; průtoková cytometrie; Genome, Plant; polyploidie; Chromosomes, Plant; Polyploidy; hybridizace nukleových kyselin; Cell Nucleus; Evropa; Genome Size; Flow Cytometry; chromozomy rostlin; délka genomu; Evolution, Molecular; molekulární evoluce; Propidium; Genetic Variation; Adaptation, Biological; buněčné jádro; Allium; podnebí; DNA rostlinná; biologická adaptace; Nucleic Acid Hybridization; ekosystém; propidium; Ecosystem; Climate; genetická variace; genom rostlinný